2022
DOI: 10.1186/s12870-022-03625-6
|View full text |Cite
|
Sign up to set email alerts
|

GsERF1 enhances Arabidopsis thaliana aluminum tolerance through an ethylene-mediated pathway

Abstract: Ethylene response factor (ERF) transcription factors constitute a subfamily of the AP2/ERF superfamily in plants and play multiple roles in plant growth and development as well as in stress responses. In this study, the GsERF1 gene from the wild soybean BW69 line (an Al-resistant Glycine soja line) was rapidly induced in response to aluminum stress. Quantitative real-time PCR (qRT–PCR) analysis showed that the GsERF1 gene maintained a constitutive expression pattern and was induced in soybean in response to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…ERF-VII Pop_ERFB2-1 could regulate the expression of hypoxia-responsive genes under high intracellular Zn concentrations. Li L. et al. (2022) suggested that overexpression of GsERF1 may enhance aluminum tolerance of Arabidopsis through an ethylene-mediated pathway and/or ABA signaling pathway.…”
Section: Erfs Regulate Plant Responses To Various Abiotic Stressesmentioning
confidence: 99%
“…ERF-VII Pop_ERFB2-1 could regulate the expression of hypoxia-responsive genes under high intracellular Zn concentrations. Li L. et al. (2022) suggested that overexpression of GsERF1 may enhance aluminum tolerance of Arabidopsis through an ethylene-mediated pathway and/or ABA signaling pathway.…”
Section: Erfs Regulate Plant Responses To Various Abiotic Stressesmentioning
confidence: 99%
“…PCR products were detected by 1% agarose gel electrophoresis (GenStar Kit, GenStar Development Company, Calgary, AB, Canada), and the purified PCR products were inserted into the polyclonal site of the zero-background clone pLB vector (Tiangen Lethal Based Fast Cloning Kit, Beijing, China). The fusion vector GmABR1-pLB was transformed into Escherichia coli DH5α ( Li et al., 2022 ). The positive clones of GmABR1 gene were identified by PCR and enzyme digestion, and the CDS sequence of GmABR1 gene was obtained by sequencing [Sangon Biotech (Shanghai) Co., Ltd., China] ( Wen et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…They can specifically bind cis -elements in the promoter region of downstream defense genes including activating or inhibiting the expression of downstream stress-responsive genes through positive and negative regulation, and thus participate in the response to plant stress ( Kumar and Sharma, 2021 ). The AP2/ERF transcription factor contains one or two conserved AP2/ERF domains consisting of approximately 58-70 amino acids which are involved in DNA binding ( Li et al., 2022 ). The AP2/ERF domain consists of three β folds and one amphiphilic α helix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other significant DEGs encoding TFs that have been implicated in aluminum or other abiotic stress responses in previous studies include those encoding ERF in Arabidopsis thaliana (Li et al, 2022), NAC in Solanum lycopersicum (Jin et al, 2020), and MYB in Zea mays (Chen et al, 2018). Overall, most of the TFs obtained in this study were also reported in tea plant, rice and Arabidopsis in response to Al-toxicity (Li et al, 2017;Li et al, 2018) and in finger millet in response to drought and for nutraceutical characteristics (Hittalmani et al, 2017).…”
Section: Differentially Expressed Genesmentioning
confidence: 99%